Cellular mechanisms underlying the inhibitory effect of flufenamic acid on chloride secretion in human intestinal epithelial cells - Pawin Pongkorpsakol (2018)
© 2017 The Authors Intestinal Cl− secretion is involved in the pathogenesis of secretory diarrheas including cholera. We recently demonstrated that flufenamic acid (FFA) suppressed Vibrio cholerae El Tor variant-induced intestinal fluid secretion via mechanisms involving AMPK activation and NF-κB-suppression. The present study aimed to investigate the effect of FFA on transepithelial Cl− secretion in human intestinal epithelial (T84) cells. FFA inhibited cAMP-dependent Cl− secretion in T84 cell monolayers with IC50 of ∼8 μM. Other fenamate drugs including tolfenamic acid, meclofenamic acid and mefenamic acid exhibited the same effect albeit with lower potency. FFA also inhibited activities of CFTR, a cAMP-activated apical Cl− channel, and KCNQ1/KCNE3, a cAMP-activated basolateral K+ channel. Mechanisms of CFTR inhibition by FFA did not involve activation of its negative regulators. Interestingly, FFA inhibited Ca2+-dependent Cl− secretion with IC50 of ∼10 μM. FFA inhibited activities of Ca2+-activated Cl− channels and KCa3.1, a Ca2+-activated basolateral K+ channels, but had no effect on activities of Na+–K+–Cl− cotransporters and Na+–K+ ATPases. These results indicate that FFA inhibits both cAMP and Ca2+-dependent Cl− secretion by suppressing activities of both apical Cl− channels and basolateral K+ channels. FFA and other fenamate drugs may be useful in the treatment of secretory diarrheas.